2013
DOI: 10.1007/s11357-013-9559-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human longevity by SIRT3 single nucleotide polymorphisms in the prospective study “Treviso Longeva (TRELONG)”

Abstract: Human sirtuins are seven proteins with deacetylase activity that are emerging as key modulators of basic physiological functions. Some evidence links SIRT3 to longevity in mammals. This study aimed to investigate whether variants within SIRT3 gene were associated to human longevity. We analyzed 549 genomic DNA collected during the prospective study "Treviso Longeva," including elderly over 70 years of AGE (2014) age from the municipality of Treviso, a small city in the northeast of Italy. We genotyped SIRT3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 23 publications
(36 reference statements)
1
43
1
Order By: Relevance
“…The failure of whole-body SIRT1 overexpression to extend the life span may be due to untoward effects on cancer, which counteract the observed slowing of aging in these mice (Herranz et al 2010). Finally, in humans, a link between SNPs at the SIRT3 locus and longevity has also been described (Albani et al 2013). All told, the above body of work strongly supports the proposal that sirtuins are conserved mediators of longevity.…”
Section: Sirtuins and Agingmentioning
confidence: 60%
“…The failure of whole-body SIRT1 overexpression to extend the life span may be due to untoward effects on cancer, which counteract the observed slowing of aging in these mice (Herranz et al 2010). Finally, in humans, a link between SNPs at the SIRT3 locus and longevity has also been described (Albani et al 2013). All told, the above body of work strongly supports the proposal that sirtuins are conserved mediators of longevity.…”
Section: Sirtuins and Agingmentioning
confidence: 60%
“…Multiple studies have shown declines in SIRT activity or levels with age in different organisms, tissues, and cells types [41, 4852]. SIRT6 and SIRT7 knockout mice display progeroid phenotypes and have shorter lifespans than controls [53, 54], and SIRT3 polymorphisms have been associated with longevity in human populations [55]. Sirtuins play a protective role in multiple aging-related diseases including neurodegenerative disorders, hearing loss, cardiovascular disease, and disorders of glucose and lipid metabolism [21, 56, 57].…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%
“…Interestingly, increased expression of SIRT3 may be linked with longevity in humans. The presence of SNP rs11555236 in linkage disequilibrium with the putative functional enhancer region of SIRT3, which is a part of variable number of tandem repeat (VNTR) element located within a SIRT3 intron (4,12), has been reported to be associated with increased longevity in some human populations (4,12,131). SIRT3 expression was higher in peripheral blood mononuclear cells from individuals homozygous for this variant (4).…”
Section: Fig 2 Subcellular Localization Of Mammalian Sirtuinsmentioning
confidence: 99%
“…The presence of SNP rs11555236 in linkage disequilibrium with the putative functional enhancer region of SIRT3, which is a part of variable number of tandem repeat (VNTR) element located within a SIRT3 intron (4,12), has been reported to be associated with increased longevity in some human populations (4,12,131). SIRT3 expression was higher in peripheral blood mononuclear cells from individuals homozygous for this variant (4). Conversely, SIRT3 expression and activity decline in response to high-fat feeding (9,59,77,111), in insulin resistance (174), and in human subjects with the metabolic syndrome (59).…”
Section: Fig 2 Subcellular Localization Of Mammalian Sirtuinsmentioning
confidence: 99%